The 3D Model in Analysing the Relations of Professional Demands during Group Trainings „Anchoring the Professional Balance State”, or where it disappeared their relationships with Psychosocial Factors related to Professional Activity? - Mariana ZUBENSCHI (Eastern European Journal of Regional Studies)
This article deals with the systemic and atomic approach issues of investigating the post-intervention outcomes. The concept of psychosocial modelling was to ensure the professional balance of doctors, teachers and social workers. Thus, data analysis revealed that some psychosocial factors that had significant relationships at the end of the formation "Anchoring the Professional Balance State" did not show the same Pearson significance chart. These facts have led us to study another kind of significant Pearson relations, the pre-intervention variables in their relationship with post-intervention, so the significant relationships identified have explained why in the case of complex variables some of them contribute to trainings and others may disappear following the same trainings sessions. This fact made us to structure the data that we received in a 3D model, which, besides facilitating the analysis of the obtained Pearson relations, also explained the phenomenon of complex psychosocial variables. The article, only will discuss about the case of the complex variable – Professional Demands, in the significant Pearson relations identified with the other investigated factors (Professional Activity and Health State).